2002
DOI: 10.1111/j.1748-5827.2002.tb00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of the sacrotuberous ligament for the treatment of coxofemoral luxation in dogs

Abstract: A surgical technique is described for transposition of the sacrotuberous ligament to replace the teres ligament in the treatment of coxofemoral luxation in dogs. Ten dogs with coxofemoral luxation were treated using this technique and all animals regained full limb function within two months of surgery. It is suggested that the technique could be employed in dogs suffering from all types of hip luxations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
11
0
4
Order By: Relevance
“…1,2,9,10,[13][14][15][16][17][18][19][20][21][22] The most common complication in the present study was reluxation, which occurred in 7 (11%) dogs, with reluxation occurring within the first 2 weeks after surgery in 4 of the 7 (5/8 hip joints). 1,2,9,10,[13][14][15][16][17][18][19][20][21][22] The most common complication in the present study was reluxation, which occurred in 7 (11%) dogs, with reluxation occurring within the first 2 weeks after surgery in 4 of the 7 (5/8 hip joints).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,9,10,[13][14][15][16][17][18][19][20][21][22] The most common complication in the present study was reluxation, which occurred in 7 (11%) dogs, with reluxation occurring within the first 2 weeks after surgery in 4 of the 7 (5/8 hip joints). 1,2,9,10,[13][14][15][16][17][18][19][20][21][22] The most common complication in the present study was reluxation, which occurred in 7 (11%) dogs, with reluxation occurring within the first 2 weeks after surgery in 4 of the 7 (5/8 hip joints).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,9,10,[13][14][15][16][17][18][19][20][21][22] Several biomechanical studies 22-24 of toggle rod stabilization have been published, but little information is available on postoperative outcomes in dogs that have undergone toggle rod stabilization for treatment of hip joint luxation or on factors associated with outcome. 1,2,9,10,[13][14][15][16][17][18][19][20][21][22] Several biomechanical studies 22-24 of toggle rod stabilization have been published, but little information is available on postoperative outcomes in dogs that have undergone toggle rod stabilization for treatment of hip joint luxation or on factors associated with outcome.…”
mentioning
confidence: 99%
“…Coxofemoral luxations (CFL) are the most common joint luxations in small animals, representing 90% of luxations, the vast majority of which are traumatic in nature . Myriad closed and open reduction and repair techniques have been described, and there are no published data to support the superiority of any of these techniques over another . In recent years, toggle rod techniques have increased in popularity, and numerous reports have been published regarding their mechanical performance and efficacy .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Myriad closed and open reduction and repair techniques have been described, and there are no published data to support the superiority of any of these techniques over another. [8][9][10][11][12][13][14][15][16] In recent years, toggle rod techniques have increased in popularity, and numerous reports have been published regarding their mechanical performance and efficacy. 17,18 This may result from relative ease of application as well as the existence of dedicated implant systems and instrumentation that are also used for a variety of other procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, open reduction techniques are favored and include capsulorrhaphy and extracapsular suture stabilization, 4,5,7,10 transarticular pinning, 1,3,4,7,11,12 toggle pin fixation, 1,4–6,8,12–17 fascia lata loop stabilization, 4,6 transposition of the greater trochanter, 1,3–5,7,18 anchor sutures, 1,19 figure 8‐shaped suture (prosthetic capsule reconstruction), 20 triple pelvic osteotomy, 1,21 excision arthroplasty, 1,3,5,8,22 and total hip replacement 1,3,23,24 . Kiliç et al reported repair of luxated hip joints in dogs with a polyester suture passed through a femoral tunnel and attached to cortical screws placed in the acetabulum and femur 25 …”
mentioning
confidence: 99%